(untitled) (Journal of the College of Basic Education, 2026)
The study aims to achieve integration between Islamic creed and behavior in raising a generation committed to Islamic values, considering the Islamic creed as the foundation for both individual and collective behavior. The significance of the study lies in its role in promoting ethical and educational values, contributing to the development of a stable and balanced society. The study seeks to illustrate how Islamic values can be instilled in the hearts of young generations and linked to practical behavior to face contemporary challenges. The study problem lies in the gap between creed and behavior in the lives of Muslims today, raising the central question: How can the integration between Islamic creed and behavior be achieved in raising a generation committed to Islamic values amid contemporary challenges? The study adopts a descriptive-analytical methodology by examining Islamic texts and analyzing their practical applications. The study concludes that the integration between creed and behavior strengthens the Muslim identity, leads to social stability, and reinforces adherence to ethical values. .